2007
DOI: 10.1080/02770900701364031
|View full text |Cite
|
Sign up to set email alerts
|

Food Allergy as a Risk Factor for Asthma Morbidity in Adults

Abstract: Self-reported allergy to foods was associated with worse outcomes, suggesting that food allergy may be a risk factor for increased asthma morbidity in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 37 publications
2
23
0
3
Order By: Relevance
“…FA has been recently found to be a major risk factor for severe asthma and life-threatening asthma episodes. Several smaller studies have identified food sensitization as a significant risk factor for severe asthma 25, 26. Roberts and colleagues reported 54% of children with asthma requiring intubation for a severe asthma exacerbation had food sensitization, compared with 10% of hospitalized children with asthma at the same hospital 27.…”
Section: Discussionmentioning
confidence: 99%
“…FA has been recently found to be a major risk factor for severe asthma and life-threatening asthma episodes. Several smaller studies have identified food sensitization as a significant risk factor for severe asthma 25, 26. Roberts and colleagues reported 54% of children with asthma requiring intubation for a severe asthma exacerbation had food sensitization, compared with 10% of hospitalized children with asthma at the same hospital 27.…”
Section: Discussionmentioning
confidence: 99%
“…12 Several studies have indicated that having food allergy may be a risk for problematic asthma, and having asthma may be a risk for severe/fatal food allergy. 12,54,65 Boys appear to be at higher risk than girls, 12 and perhaps women more than men. 66 One study showed a higher risk for increased affluence.…”
Section: Risk Factors Genetics and Racial And Ethnic Differencesmentioning
confidence: 91%
“…In adults, there is evidence that being allergic to more than one food is associated with an increase frequency of oral steroid use and a higher risk of lifetime hospitalizations and emergency department attendances (50). In children, a study showed that having a milk or peanut allergy was associated with an increased number of hospitalizations ( p  = 0.009, 0.016) (51).…”
Section: Asthma Triggered By Food Allergensmentioning
confidence: 99%